Synthesis and characterization of Nano-Zno particles as solar photocatalyst prepared by Sol-gel method - M. M., Ba-Abbad; A. A. H, Kadhum; A. B., Mohamad; M. S., Takriff; K., Sopian (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.